Insights Into Intraplate Stresses and Geomorphology in the Southeastern United States. Issue 15 (2nd August 2019) - Murphy, Benjamin S.; Liu, Lijun; Egbert, Gary D.
Abstract: The stress field in the eastern United States is commonly considered to be broadly uniform and due to homogeneous far‐field forces; however, modern and geologic stress indicators in this region show substantial heterogeneity. Using CitcomS to model stresses based on simple input density, temperature, and viscosity fields, we show that local isostasy is key in explaining the intraplate stress field in the southeastern United States. Crustal thickness variations appear to be most important in reproducing observations, although we slightly better match the observed stress field by including variable crustal viscosity informed by magnetotelluric imaging. Our results demonstrate that local gravitational body forces can substantially reorient far‐field stresses and thereby influence patterns of intraplate seismicity. We also show that variable crustal viscosity encourages a steepening of isostatic topography in the southeastern United States; this observation suggests that a sharp boundary in crustal strength may be important in explaining the apparently long‐lived Appalachian topographic escarpment. Plain Language Summary: The origin of stresses within tectonic plates, and hence the ultimate driving force of earthquakes far from plate boundaries, is a contentious topic. Historically, the geoscience community has viewed intraplate stress patterns as being simply the result of forces applied along plate edges. However, this paradigm does not explain why earthquakes far from plate boundaries cluster into discrete seismic zones, nor does it explain the diverse mechanisms of intraplate earthquakes. Here, we consider the southeastern United States, which is thousands of kilometers from any plate boundary, but which nevertheless experiences major earthquakes, such as the 2011 Virginia earthquake that shook the nation's capital. Using numerical models, we show that forces arising from variable thickness of the Earth's crust can largely explain the stress and earthquake patterns observed in this region. Another curious feature of the southeastern United States is the steep topography of the Blue Ridge Escarpment in the Appalachian Mountains; despite having been subjected to episodic erosion for over a hundred million years, the southeastern edge of the range is surprisingly sharp. With our models, we show that weak zones within the crust beneath the Appalachians may help to explain how that steep escarpment has survived over long timescales. Key Points: Stress indicators in the southeastern United States show substantial heterogeneity Gravitational body forces from variable crustal thickness are important in explaining many features of observed stress patterns Crustal weak zones beneath the Appalachian Mountains may help maintain a sharp passive margin escarpment (the Blue Ridge Escarpment)